2022
DOI: 10.3390/life12050609
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Effect of Maternal Methyl-Group Donor Intake on Offspring’s Health and Disease

Abstract: Maternal exposure to some dietary and environmental factors during embryonic development can affect offspring’s phenotype and, furthermore, the risk of developing diseases later in life. One potential mechanism responsible for this early programming may be the modification of the epigenome, such as DNA methylation. Methyl-group donors are essential for DNA methylation and are shown to have an important role in fetal development and later health. The main goal of the present review is to summarize the available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Animal studies suggest that a higher multivitamin consumption during gestation increases body weight, food intake, and characteristics of the MS of the progeny ( 57 59 ). The number of studies investigating the role of altered DNA methylation patterns caused by maternal vitamin intake (especially the vitamins playing a role in the one-carbon metabolism and vitamin D) during pregnancy in the development of obesity and related metabolic changes has increased recently ( 58 , 60 ) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies suggest that a higher multivitamin consumption during gestation increases body weight, food intake, and characteristics of the MS of the progeny ( 57 59 ). The number of studies investigating the role of altered DNA methylation patterns caused by maternal vitamin intake (especially the vitamins playing a role in the one-carbon metabolism and vitamin D) during pregnancy in the development of obesity and related metabolic changes has increased recently ( 58 , 60 ) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed an association between altered DNA methylation patterns of genes (most investigated genes: IGF2, H19, LINE-1, ZAC1, MEG3) and maternal intake of methyl-group donors on offspring birth weight ( 60 ). In these studies, the effect on progeny’s long-term health was not investigated, despite the well-described associations between adult chronic diseases and lower birth weight ( 88 ).…”
Section: Resultsmentioning
confidence: 99%
“…A diet rich in methyl-donating nutrients can quickly affect gene expression, particularly in early development, when the epigenome is being established, and can have long term consequences in adulthood [ 32 ]. Animal studies have shown that an insufficient intake of folate or choline, which are methyl-donating compounds, before or after birth leads to lasting hypomethylation of certain genomic regions [ 33 ]. In adults, a diet lacking in a methyl group leads to reduced DNA methylation, but these changes can be reversed when methyl is reintroduced into the diet [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, experimental studies with a maternal diet supplemented with choline or with resveratrol have shown the relevance of the triggered epigenetic mechanisms in the long-term neuroprotection of the offspring of mouse models of cognitive impairment [ 10 , 11 ]. Specifically, choline is a major dietary donor of methyl groups essential for DNA and histone methylation that play an important role in fetal brain development [ 12 ]. Epigenetic mechanisms of maternal choline induce long-term changes in gene expression levels affecting neurotransmission, neurotrophism, and autophagy pathways in the Ts65Dn mouse model of Down′s syndrome [ 10 ].…”
Section: Introductionmentioning
confidence: 99%